Dies irae Kroniek van het requiem - Bergé, Pieter (Leuven University Press, 2021)
The requiem (or the death mass) is one of the oldest and longest surviving genres in Western music history. For hundreds of years it only existed in its original Gregorian guise, but from about 1450 many great composers were inspired to write of masterly new death masses Dies Irae introduces the reader to these masterpieces in an accessible way, without any prior musical knowledge being required. After an introduction to the meaning and structure of the text and music of the ancient Latin Mass for the Dead, a chronicle in three parts follows that guides the reader through the history of the requiem. In separate chapters, all the major and well-known requiems (including by Mozart, Brahms, Verdi, Fauré, Britten and Webber), as well as some less popular but equally poignant works (such as the requiems by Ockeghem, Schütz, Weill, Ligeti, Stravinsky and Zimmermann). Each requiem is discussed according to a fixed pattern, so that the reader can freely browse through different periods and compositions: first each work is situated music-historically, followed by a short discussion of each part separately. By linking the discussions to one reference recording per work, the reader can immediately test the explanation against listening practice. Under the direction of Pieter Bergé, and with the cooperation of Jan Christiaens, all contributions to 'Dies Irae. Chronicle of the Requiem' written by authors who are affiliated with the Musicology research unit of KU Leuven as teachers, researchers or alumnus.